Pengaruh Aktivitas Judi Terhadap Kesehatan Dan Pandangan Hadis: Studi Kasus Di Masyarakat Medan Area - Ar Rahman, M Rifai (Nizamiyah: Jurnal Sains, Sosial dan Multidisiplin, 2025)
Gambling has become a widespread social phenomenon that significantly impacts the mental, physical, social, and economic well-being of individuals involved. This study aims to analyze the effects of gambling activities on community welfare in the Medan Area through a Mixed Methods approach that combines both quantitative and qualitative analyses. Quantitative data were obtained through a survey of 200–300 respondents using the DASS-21 scale to measure levels of stress, anxiety, and depression, while qualitative data were collected through in-depth interviews with former gamblers, religious leaders, and members of the surrounding community.The findings indicate that gambling has a detrimental effect on mental health, marked by increased stress, sleep disturbances, and emotional dependency on gambling. Physically, respondents reported irregular eating patterns and chronic fatigue as a result of gambling activities. Economically, many individuals experienced financial losses that led to family conflicts and a decline in overall well-being. Community attitudes toward gambling varied; while the majority opposed it, a portion of the population remained permissive. From an Islamic perspective, gambling is prohibited as it brings harm to both individuals and society. This study recommends community- and faith-based approaches to rehabilitate gambling addicts, alongside educational campaigns to raise awareness of the dangers of gambling.